A facile method prepared nitrogen and boron doped carbon nano-tube based catalysts for oxygen reduction. (16th February 2017) - He, Wei; Xue, Peihua; Du, Huatai; Xu, Luping; Pang, Minglei; Gao, Xueping; Yu, Jiemei; Zhang, Zhaoliang; Huang, Taizhong
Abstract: In this paper, we designed a facile method to prepare nitrogen doped CNT (N-CNT), boron-doped CNT (B-CNT) and nitrogen, boron co-doped CNT (N, B-CNT) catalysts for oxygen reduction. The microstructures of the catalysts were characterized by Raman spectroscopy, X-ray diffraction (XRD), transmission electron microscope (TEM), and X-ray photoelectron spectroscopy (XPS). The results clearly showed the successful doping of nitrogen or/and boron. The cyclic voltammetry (CV), Tafel, linear scanning voltammetry (LSV) tests confirmed that the onset potentials and peak current intensities of oxygen reduction increased in the sequence of pure CNT < N-CNT < B-CNT < N, B-CNT. The rotating disc electrode (RDE) tests proved the electron transfer number of oxygen reduction increased with the doping of nitrogen, boron and co-doping of nitrogen and boron. The N, B-CNT is a promising catalyst for oxygen reduction. Graphical abstract: Highlights: A facile methodology to dope nitrogen or/and boron to CNT is reported. Nitrogen-boron co-doped CNT is a high performance catalyst for oxygen reduction. The co-doped nitrogen and boron promote the 4-electron oxygen reduction reaction. The exchange current intensity is enhanced by co-doped nitrogen and boron.